P070 Efficacy of a novel non-covalent oral small molecule Nrf2 activator in a rat model of Inflammatory Bowel Disease. (27th May 2021) - Murray, C; Cooper, N; Lucas, C L; Manso, A S; Ray, N C; Worthington, J; Fox, J C
Abstract: Background: Inflammatory Bowel Disease (IBD) is characterised by chronic inflammation and increased oxidative stress in the intestinal mucosa of patients. NF-E2-related factor 2 (Nrf2) plays a key role in the antioxidant response by regulating the transcription of antioxidant genes as well as reducing expression of inflammatory mediators. A role for the Nrf2 pathway in IBD has been demonstrated in rodent models previously but these studies have predominantly used compounds such as Dimethyl Fumarate that are covalent Nrf2 activators that have the potential for significant off-target activities. C4X Discovery has identified C4X_6746, a novel potent and selective non-covalent Nrf2 activator, that disrupts the interaction between Nrf2 and its repressor Keap1 and is being investigated as an oral treatment for inflammatory disorders. Methods: Male Han Wistar rats were given 3% Dextran Sodium Sulphate (DSS) in drinking water for 8 days in order to induce colitis and were dosed once daily by oral gavage with vehicle, C4X_6746 (0.3, 3 or 30 mg/kg) or Cyclosporine A (CsA, 20 mg/kg). The Disease Activity Index (DAI) was assessed daily based on stool consistency, faecal blood and body weight. On study termination, the colon weight and length were measured, and additional endpoints assessed (colon macroscopic score, histology, colon markers of inflammation and antioxidant response). Results: C4X_6746 caused a dose-dependent decrease in the DAI with 30 mg/kg showing similar efficacy to the reference comparator CsA. C4X_6746 (3 and 30 mg/kg) resulted in a statistically significant reduction in the colon weight:length ratio and the macroscopic score. The compound also reduced the DSS-induced histological changes including inflammatory cell infiltrate, epithelial damage and mucosal architecture changes. Analysis of the colon tissue showed that C4X_6746 reduced inflammation (MPO activity) and upregulated the antioxidant response (SOD activity, ratio of reduced:oxidised glutathione). Efficacy of C4X_6746 in the model correlated with the dose-dependent induction of NQO1 mRNA in the colon and blood as a biomarker for Nrf2 pathway activation. Conclusion: The efficacy of C4X_6746 in the rat DSS model supports development of non-covalent oral Nrf2 activators to significantly reduce oxidative tissue damage and chronic inflammation in IBD.